Slavery and Reform in West Africa : Toward Emancipation in Nineteenth-Century Senegal and the Gold Coast. - Getz, Trevor R. (Western African studies., 2004)
A series of transformations, reforms, and attempted abolitions of slavery form a core narrative of nineteenth-century coastal West Africa. As the region's role in Atlantic commercial networks underwent a gradual transition from principally that of slave exporter to producer of "legitimate goods" and dependent markets, institutions of slavery became battlegrounds in which European abolitionism, pragmatic colonialism, and indigenous agency clashed. In Slavery and Reform in West Africa, Trevor Getz demonstrates that it was largely on the anvil of this issue that French and Br